2017
DOI: 10.1038/s41598-017-11986-4
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Acoustic Sensing for Seismic Monitoring of The Near Surface: A Traffic-Noise Interferometry Case Study

Abstract: Ambient-noise-based seismic monitoring of the near surface often has limited spatiotemporal resolutions because dense seismic arrays are rarely sufficiently affordable for such applications. In recent years, however, distributed acoustic sensing (DAS) techniques have emerged to transform telecommunication fiber-optic cables into dense seismic arrays that are cost effective. With DAS enabling both high sensor counts (“large N”) and long-term operations (“large T”), time-lapse imaging of shear-wave velocity (V S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
178
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 317 publications
(201 citation statements)
references
References 36 publications
1
178
0
Order By: Relevance
“…Several authors have observed local noise in DAS data, which we classify here. One type of noise, referred to as common‐mode noise (Ajo‐Franklin et al, ; Bakku, ; Dou et al, ) is characterized by an infinite‐velocity signal (arrives at all channels simultaneously). This is caused by local seismic disturbance near the interrogator, which vibrates the optoelectronic system and leads to an overprinted signal on all channel recordings at the same time.…”
Section: The Das Measurement Principlementioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have observed local noise in DAS data, which we classify here. One type of noise, referred to as common‐mode noise (Ajo‐Franklin et al, ; Bakku, ; Dou et al, ) is characterized by an infinite‐velocity signal (arrives at all channels simultaneously). This is caused by local seismic disturbance near the interrogator, which vibrates the optoelectronic system and leads to an overprinted signal on all channel recordings at the same time.…”
Section: The Das Measurement Principlementioning
confidence: 99%
“…Generally, DAS studies have focused on seismic wave phase information, which is sufficient to model seismic wavefield velocities, for example, in vertical seismic profiling (Daley et al, ; Mateeva et al, ), ambient noise velocity inversions (Ajo‐Franklin et al, ; Dou et al, ; Zeng et al, ), and earthquake phase identification (Ajo‐Franklin et al, ; Jousset et al, ; Lindsey et al, ; Yu et al, ). However, true ground motion amplitudes are necessary for many other seismological processing tasks, including full‐waveform inversion, AVO analysis, moment tensor inversion, and attenuation analysis, which the DAS community will likely investigate in the near future (Cole et al, ; Paitz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the PoroTomo experiment in Nevada, Wang et al (2018) also found coherent earthquake waveforms recorded at a dense DAS array and a dense geophone array from a local M L 4.3 event. Dou et al (2017) used traffic noise interferometry for seismic monitoring of the near-surface structure. Jousset et al (2018) demonstrated the possibility of using DAS data for subsurface fault zone imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Zeng et al (2017) extracted noise cross-correlation functions from a DAS array at Garner Valley, California. Dou et al (2017) used traffic noise interferometry for seismic monitoring of the near-surface structure.…”
Section: Introductionmentioning
confidence: 99%
“…DFOS with Raman scattering has already been known as distributed temperature sensing and utilized for a host of hydrological and geothermal applications (Briggs et al, 2012;Carlino et al, 2016;Curtis & Kyle, 2011;Selker et al, 2006). Recently, by exploiting changes in Brillouin and Rayleigh scattering induced by external strains, the DFOS technology has been utilized for geohazard sensing including earthquake observations (Dou et al, 2017;Jousset et al, 2018;Lindsey et al, 2017) and landslide detection (Huntley et al, 2014;Lienhart, 2015;Michlmayr et al, 2017;Picarelli et al, 2015;Schenato et al, 2017). While a few studies have explored the feasibility of DFOS for subsidence and strata deformation sensing (Murai et al, 2013;Wu et al, 2015), the understanding of data collected from borehole-embedded FO cables has remained elusive and hence precluded its use in many contexts.…”
Section: Introductionmentioning
confidence: 99%